Time variability in the annual cycle of sea ice thickness in the Transpolar Drift. Issue 12 (18th December 2015) - Hansen, E.; Gerland, S.; Høyland, K. V.; Pavlova, O.; Spreen, G.
Abstract: The annual cycle of modal and mean sea ice thickness was derived from upward looking sonar ice thickness observations (1990–2011) in Fram Strait. The average annual peak‐to‐trough amplitude of the mode of 0.54 m is superimposed on interannual variability with peak‐to‐trough amplitudes of 0.73 m on time scales of 6–8 years, which again is superimposed on a long‐term trend of −0.55 m/decade over the observation period. The long‐term trend is stronger for April than for August, the average months of maximum and minimum modal thickness. As a result, the annual peak‐to‐trough modal thickness amplitude was reduced by 30% between the 1990s and the 2000s. The average annual peak‐to‐trough amplitude of the mean ice thickness of 1.20 m is also superimposed on interannual variability, with as much as 0.97 m thickness change over only 3 years. These two modes of variability are superimposed on a long‐term trend of −0.35 m/decade through the entire data set. In contrast to the modal thickness, the long‐term trend is weaker for the average month of maximum mean thickness (June), than for the average month of minimum (September). Therefore, the annual peak‐to‐trough amplitude of the mean ice thickness increased by 14% between the 1990s and the 2000s. Key Points: The 1990–2011 thinning trend in ice thickness in Fram Strait displays seasonality The annual peak‐to‐trough amplitude of the modal thickness decreased by 30% during 1990–2011 The annual peak‐to‐trough amplitude of the mean ice thickness increased by 14% during 1990–2011